2016
DOI: 10.1097/meg.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of anxiety and depression are frequent in patients with acute hepatitis C and are not associated with disease severity

Abstract: HADS data in acute HCV infection indicate that anxiety and depression do not correlate with severity of the disease, mode of acquisition, lost to follow-up and sustained virological response rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Limitations of this study include the limitations of the instrument to measure anxiety or depression. While the HADS has been used to assess the prevalence of anxiety and depression in clinical trials of many diseases, [34][35][36][37] including moderate-to-severe plaque psoriasis, 29,[38][39][40][41] some studies have proposed that HADS is best suited for screening rather than assessment of severity of anxiety and depression over time. [42][43][44] In addition, the optimal HADS score cut-off to define clinically important improvement in symptoms of anxiety or depression remains undertermined.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study include the limitations of the instrument to measure anxiety or depression. While the HADS has been used to assess the prevalence of anxiety and depression in clinical trials of many diseases, [34][35][36][37] including moderate-to-severe plaque psoriasis, 29,[38][39][40][41] some studies have proposed that HADS is best suited for screening rather than assessment of severity of anxiety and depression over time. [42][43][44] In addition, the optimal HADS score cut-off to define clinically important improvement in symptoms of anxiety or depression remains undertermined.…”
Section: Discussionmentioning
confidence: 99%
“…Forced expiratory volume has been used as index of severity of cystic fibrosis. Aminotransferase and bilirubin levels have been used to assess the severity of hepatitis.…”
Section: Severity Of Physical Illnessesmentioning
confidence: 99%
“…Women with NAFLD are more likely to develop anxiety and depression than men and had a higher incidence of steatosis ( Choi et al, 2021 ). The study by Zhang et al (2020) found that the feeling of being discriminated against in daily life was the main influencing factor for anxiety and depression in patients with acute hepatitis B. Anxiety and depression were common in acute hepatitis C infection, but it was not related to the severity of the disease, the method of infection, or the rate at which patients were lost to follow-up ( Deterding et al, 2016 ). Even for high-risk patients with severe mental disorders, direct antiviral therapy had no effect on anxiety or depression during or after treatment for chronic hepatitis C infection ( Gallach et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%